Training-induced increases in sea-level performance are enhanced by acute intermittent hypobaric hypoxia - Meeuwsen, T.; Hendriksen, I. J.; Holewijn, M. (European Journal of Applied Physiology, 2001)
The goal of this study was to investigate to what extent intermittent exposure to altitude in a hypobaric chamber can improve performance at sea-level. Over a 10-day period, elite male triathletes trained for 2 h each day on a cycle ergometer placed in a hypobaric chamber. Training intensity was 60-70% of the heart rate reserve. Eight subjects trained at a simulated altitude of 2.500 m (hypoxia group), the other eight remained at sea-level (sea-level group). Baseline measurements were done on a cycle ergometer at sea-level, which included an incremental test until exhaustion and a Wingate Anaerobic Test. Nine days after training in hypoxia, significant increases were seen in all important parameters of the maximal aerobic as well as the anaerobic test. A significant increase of 7.0% was seen in the mean maximal oxygen uptake per kilogram body weight (VO2max), and the mean maximal power output per kilogram body weight (Wmax) increased significantly by 7.4%. The mean values of both mean power per kilogram body weight and peak power per kilogram body weight increased significantly by 5.0%, and the time-to-peak decreased significantly by 37.7%. In the sea-level group, no significant changes were seen in the above-mentioned parameters of both the maximal aerobic and the maximal anaerobic test at the second post-test. The results of this study indicate that intermittent hypobaric training can improve both the aerobic and the anaerobic energy-supply systems.